Test of Antibacterial Activity of Sea Cucumbar Extract (Holothuria Scabra) Against Growth of Vibrio Harveyi Bacteria on Tiger Shrimp (Paneus Monodon) - Arbaeyah '; Dessy Yoswaty; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Tiger shrimp is one of the most popular fishery products in the world. H. scabra has been shown to be a potential antibacterial agent. Potential antibacterial extract from H. scabra can be derived from the presence of antibacterial agents i.e steroids, saponins and triterpenoids. Bacteria V. harveyi is one of pathogenic bacteria which according to some research can cause disease in shrimp cultivation. Diseases caused by vibrio bacteria are usually called vibriosis. The purpose of this research is to know the effect of antibacterial activity of sea cucumber extract (H. scabra) on the growth of V.harveyi bacteria on tiger shrimp (P. monodon), to know the character and structure of bacteria which is inhibited by sea cucumber extract (H. scabra). This research was conducted in August 2016 in Marine Microbiology Laboratorium of Riau University. Based on the results of research that sea cucumber extract has the ability to inhibit the activity of V. harveyi bacteria. The mean value of the inlet zone is 4.06 - 6.26 mm.Keywords: Sea cucumber, Antibacterial, V. harveyi